Necrotizing fasciitis and fatal septic shock associated with Streptococcus constellatus - Rajack, Fareed; Medford, Shawn; Naab, Tammey (Autopsy and Case Reports, 2024)
Streptococcus constellatus is usually a benign, commensal bacteria but has increased incidence in blood cultures and abscesses. This pathogenic involvement is most prevalent in individuals with underlying medical conditions, such as solid tumors and type 2 diabetes mellitus, as well as in cases of community-acquired infections. We report a 43-year-old male with a right medial thigh ulcer and necrotic scrotal skin. The wound culture from surgical debridement grew Streptococcus constellatus, and histology was consistent with stage III necrotizing fasciitis. Regardless of etiology, the mortality rate of patients with necrotizing fasciitis is greatly decreased with early intervention and thorough surgical debridement.